Audio Branding: Brands, Sound and Communication - Bronner, Kai; Hirt, Rainer (Nomos Verlagsgesellschaft mbH & Co. KG, 2009)
Audio Branding, also known as Sound Branding or Sonic Branding, describes brand communication through sound, using brand sound elements like an audio logo, a brand song or a brand voice. So far, brands have spent a lot of time and money on visual branding while sound hasn"t been treated as a brand element that needs to be designed. The emerging of new media and devices with built-in audio delivery, such as podcasts, audiobooks, smartphones, expands the opportunities for Audio Branding but also increases the risks of causing noise pollution and a sonic mess.Consequently, the use of sound in brand communication demands careful attention. The articles in this book deal with functions of sound, the basics and principles of brand communication and Audio Branding, multi-sensory aspects of brand communication and legal matters concerning sound marks, among others. In case studies on projects with international brands, leading experts provide insight into what Audio Branding actually means in practice. This compilation is based on the German publication Audio-Branding that was released in 2007.Main chapters:- basics of sound and branding- the beginnings of audio branding- basics and principles of audio branding- multi-sensory design- legal aspects- case studies